Goblins don't play video games - Dadey, Debbie; Jones, Marcia (Marcia Thornton); Gurney, John; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1999)
There are some pretty weird grown-ups living in Bailey City. But could the new computer teacher really be the Great Goblin from Melody's video game? The Bailey School Kids are going to find out!
"Little apple."
"A Little apple paperback."
G4
Keywords: Schools -- Juvenile fiction; Young adult fiction